Análisis Comparativo del Rendimiento de los Módulos Fotovoltaicos Monocristalino y Policristalino bajo Condiciones Climáticas de Fusagasugá - García Vera, Yimy Edisson; Sanabria Pérez, Lina Fernanda; Cruz Pardo, Luz Angela; Montufar Benavides, Carlos Humberto (Ingeniería, 2019)
Context: To meet the world’s energy demand, photovoltaic solar energy has emerged as a sustainable, environmentally friendly renewable energy, used as an alternative to mitigate climate change caused by the use of energy from fossil fuels. therefore, it is very important to study the behavior of these photovoltaic modules under real operating conditions. Method: Two stand-alone photovoltaic systems were implemented, one of monocrystalline technology and another polycrystalline, each of data acquisition system of temperature, humidity, voltage and current, which are acquired in a synchronized manner over a period of 3 months, under local weather conditions of Fusagasugá. Results: The temperature, humidity, irradiance, voltage and current data are used to obtain curves showing the energy performance of the polycrystalline and monocrystalline modules. Conclusions: The results of this study can help predict the output characteristics of photovoltaic system, mainly when the weather conditions change such as temperature, humidity and irradiance. A better performance of the monocrystalline module in the polycrystalline is evidenced.